2013
DOI: 10.1111/anae.12182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaesthetic technique on mortality following major lower extremity amputation: a propensity score‐matched observational study

Abstract: SummaryWe investigated whether the type of anaesthesia affects mortality and length of stay after non-traumatic major lower extremity amputations. A total of 1365 eligible patients who were operated on between 2002 and 2010 were included in the final analysis. Propensity score matching was used to produce 475 matched pairs of patients undergoing operation with either general or regional anaesthesia. We found that 30-day mortality was significantly greater in the general anaesthesia group compared with the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 30 publications
3
30
1
Order By: Relevance
“…[1][2][3][4][5][6][7] Patient's pre-operative condition, including their ASA status, presence of septic shock and site of amputation undertaken are significant predictors of post-operative in hospital mortality rate and ICU admission rate. Patients with pre-operative septic shock, ASA 4 status and undergoing AKA should be regarding as high risk group, and appropriate level of intra-operative monitoring and post-operative disposition should be arranged.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7] Patient's pre-operative condition, including their ASA status, presence of septic shock and site of amputation undertaken are significant predictors of post-operative in hospital mortality rate and ICU admission rate. Patients with pre-operative septic shock, ASA 4 status and undergoing AKA should be regarding as high risk group, and appropriate level of intra-operative monitoring and post-operative disposition should be arranged.…”
Section: Resultsmentioning
confidence: 99%
“…One large scale retrospective study showed that 30-day mortality is significantly higher in patients undergoing MLEA under general anaesthesia compared with regional anaesthesia with an odds ratio of 1.5. 7 However when further subgroup analyses was done for patients that underwent knee amputation surgery under peripheral nerve block alone, the authors was unable to detect any significant difference of the effect of anaesthesia on 30-day mortality rate.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations